Islamic Moderation in Context: Ulama and Religious Communication in East Aceh - Bahtiar; Abdullah; Sukiman (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This article examines the religious communication strategies of ulama (Islamic scholars) in East Aceh; analyzing their role in promoting religious moderation. Using Lessl’s theory that argues religious communication is inherently metaphorical and involves metaphysical referents, this article highlights the important role of da’wa in encouraging the acceptance of the idea of moderation within the community. This article was based on qualitative research and two months field observations of Abati Aramia and Abah Zein’s pengajian (recitation), two young and influential ulama in East Aceh. The data validation process used data triangulation by connecting field data, observation and theory to get a complete understanding of the phenomenon. This paper argues that the influence of ulama in introducing religious moderation, particularly state-promoted ideas, into local contexts is crucial. Abah Zein employs a dialogical approach, making his da’wah interactive and responsive to societal needs, while Abati Aramia emphasizes collective dialogue and consensus for maintaining societal harmony. From this study it is concluded that the ulama’s communication strategies are integral to promoting Islamic moderation, bridging the gap between religious teachings and the everyday challenges faced by the community.